Incubating policy for economic transformation: Lessons from Nepal - David A. Booth (Overseas Development Institute (ODI), 2018)
A substantial body of theory now exists on economically sound and politically smart ways of jump-starting progress in poor developing countries. At several levels, however, the practice is lagging behind the theory, meaning there is much to learn from any new experiences suggesting precisely how to advance this agenda. This paper reports some early successes from a UK Department for International Development-funded programme in Nepal, the Economic Policy Incubator. Although this programme is at a relatively early stage, it has some highly transferable features and has already generated valuable lessons. (...)
Keywords: 330